(untitled) (LEARNing Landscapes, 2022)
This article considers the experience of a literary professor working to maintain connections and creativity—as well as model pedagogy—in the context of Fall 2020. The author created invitations for undergraduate and graduate students to reflect on experiences and engage with texts/course readings, using poetic and visual choices for composing. This article includes examples of creations from this context, including mentor text work, as well as implications for creativity in online instruction.